Assemblages and chemical composition of amphiboles in rocks of the Jilove Belt, Central Bohemia - Fediukova,E.; Fediuk,F. (Journal of the Czech Geological Society, 2000)
Amphiboles constitute, along with feldspars and quartz, the most widespread minerals of the Proterozoic metavolcanic Jilove Belt. They occur in major amount in its metabasaltic and metaandesitic rocks, but they are locally also present as a characteristics subordinate constituent in acid members of the belt, namely in orthogneisses. Many species of amphiboles can be distinguished here: dominant magnesiohornblende, abundant actinolite and less common tschermakite, ferrotschermakite, ferrohornblende, ferroactinolite, pargasite, ferropargasite and edenite. Cummingtonite is widespread. In contrast, typical alkali amphiboles and NaCa amphiboles are absent. In most samples, two up to four of the above mentioned species usually occur. The present assemblages resulted from an interaction of the bulk rock chemistry with pre-Palaeozoic regional and Variscan contact metamorphism. Relictic amphiboles of the magmatic stage, represented by high-alumina members, are present in subordinate amount only.
Keywords: Amphiboles; electron microprobe; matamorphism; Proterozoic; volcanics; Bohemian Massif